2022
DOI: 10.3389/fmicb.2022.907888
|View full text |Cite
|
Sign up to set email alerts
|

NLR, A Convenient Early-Warning Biomarker of Fatal Outcome in Patients With Severe Fever With Thrombocytopenia Syndrome

Abstract: BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that greatly threatens public health. This study aimed to examine a convenient early-warning biomarker of fatal outcomes in patients with SFTS to reduce mortality.MethodsA retrospective cohort study was performed, and patients with confirmed SFTS were enrolled in the top two hospitals in Anhui Province, China from 1 May 2016 to 31 October 2019. The clinical symptoms, laboratory indicators, and treatment data of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…From the perspective of laboratory indicators, high viral load has been revealed as one of the indicators of poor prognostic for SFTS in several studies, but studies performed to explore the association between viral RNA loads of DBV and the occurrence of IPA are currently lacking (Wei et al, 2022). Bae et al (2020) reported that the viral load level was significantly higher in the IPA group, which corresponded with our result but did not go into more detail via regression analysis.…”
Section: Discussionsupporting
confidence: 82%
“…From the perspective of laboratory indicators, high viral load has been revealed as one of the indicators of poor prognostic for SFTS in several studies, but studies performed to explore the association between viral RNA loads of DBV and the occurrence of IPA are currently lacking (Wei et al, 2022). Bae et al (2020) reported that the viral load level was significantly higher in the IPA group, which corresponded with our result but did not go into more detail via regression analysis.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have described early hematological predictors of poor outcomes in SFTS, including viral load [ 16 ]; organ damage indicators such as platelet (PLT), lactate dehydrogenase (LDH), creatine kinase (CK), activated partial thromboplastin time (APTT), and blood urea nitrogen (BUN) [ 17–19 ]; and inflammatory-related indicators such as neutrophil counts, lymphocyte counts, interleukin (IL)-10, IL-1β, interferon inducible protein (IP)-10, and IL-6 [ 20 , 21 ]. Among these indicators, viral load is the most important prognostic indicator, its concentration directly reflects the replication of pathogens in vivo to evaluate the severity of disease.…”
mentioning
confidence: 99%
“…The NLR is an inflammatory indicator that assesses the severity and prognoses of SFTS. Wei et al identified that NLR was one independent prognostic factor for SFTS mortality with convenience and lower expense 18 . Liu et al revealed that an elevated NLR correlated with higher incidences of MODS and increased risks of short‐term mortality in SFTS patients 24 .…”
Section: Discussionmentioning
confidence: 99%